2019
DOI: 10.1111/pirs.12375
|View full text |Cite
|
Sign up to set email alerts
|

Wage returns to interregional mobility among Ph.D graduates: Do occupations matter?

Abstract: This paper addresses the wage returns to interregional mobility among Italian Ph.D workers. We control for selection bias in both migration and occupation choice by estimating a double sample selection model. While OLS estimates indicate a positive wage premium of mobility across all types of occupations examined, wage equations estimated by correcting for double sample selection evidence a wage penalty for movers within academia, no effects for movers carrying out R&D activities but positive returns if they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…International mobility of high-educated people and researchers has positive consequences on their occupational prospects and careers, both in the short-and long-run (Ermini et al, 2019). Despite it, women in academia have a lower mobility with respect to their male counterparts, experiencing more often work-family conflicts that tend to limit their traveling during their academic careers (González -Ramos and Bosch, 2012;Jöns, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International mobility of high-educated people and researchers has positive consequences on their occupational prospects and careers, both in the short-and long-run (Ermini et al, 2019). Despite it, women in academia have a lower mobility with respect to their male counterparts, experiencing more often work-family conflicts that tend to limit their traveling during their academic careers (González -Ramos and Bosch, 2012;Jöns, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in high-skilled mobility is also a consequence of the weakening of research and university systems of sending countries (the "brain drain" process), and the increase in skilled demand and improvements in higher education of host countries (the "brain gain" process; Boeri et al, 2012). At the micro-level, academic mobility has positive consequences on occupational prospects and careers of researchers, both in the short-and long-run (Ermini et al, 2019). For European researchers, experiencing scientific mobility is a way to advance their careers (Ackers, 2005;Mahroum, 2000;Morano-Foadi, 2005), but only a few studies focused on gender differences in opportunities for international scientific mobility (Deitch and Sanderson, 1987;Rosenfeld and Jones 1987;Mason et al, 2013;Cohen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At the macro level, highly educated young people represent several short-and longterm gains for institutions and countries, which are increasingly seeking to recruit international students and retain them after graduation (Avveduto, 2012). At the micro level, empirical evidence in academic mobility has suggested that the international migration of educated and skilled people can have positive effects on their future employment prospects and careers, leading to higher salaries and better roles (Ermini et al, 2019). As a consequence, occupational prospects and careers may differ between those who have pursued an experience abroad and those who studied only in their home country.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, mobility of PhD holders may be even more important, given the growing competition for finding a job related to their training and acquiring access within academia (Ballarino & Colombo, 2010). Despite the rising importance of doctoral mobility, international mobility during PhD studies is an under-studied phenomenon, as most studies tend to concentrate on graduates' and PhD holders' mobility (Ermini et al, 2019;Panichella, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation